Cystic dilations of the bile duct - Perrier, José P; Delgado, Bolívar; Gateño, Nisso; Piñeyro, Alberto (Cirugía del Uruguay, 1994)
Four cases of cystic dilatation of the extrahepatic biliar viae are presented together with a revision of the tapie. The authors come to the conclusion that surgery is the best treatment and that in the case of the most frequent cases, the so-cal/ed choledochus cysts, ideal treatment consists of total resection of the cyst and biliodigestive derivation. Interna/ derivations are a bad solution due to the high incidence of complications that make reoperation neccesary and do not avoid cancer development, a frequent evolutive complication of this pathology.